A study on effectiveness of pedestrian bridge utilization - Nurul Hidayah, Kadzim (2012)
The study on The effectiveness of Pedestrian Bridge Utilization is to determine the factors that effecting the usage of pedestrian bridge. The effectiveness of the pedestrian bridge is depends on amount of use by pedestrian. However, they are costly and may not be used by pedestrian if not planned properly. The use rate of two pedestrian bridges was observed in the Jalan Lin Chen Mei, Sitiawan, Perak and Lebuhraya Tun Razak, Kuantan, Pahang. Three set of the data has been collected at two different location of pedestrian bridge; traffic volume survey, pedestrian volume survey and pedestrian interview survey. Volume of traffics and pedestrian crossing the roads are recorded by manual and electronically by using video camera. A survey was conducted among pedestrians using those bridges and crossing at street level. The study from data analysis has shown that the usage rate of pedestrian bridge is linearly proportionate with the traffic volume. In the present database, the frequent use of the bridge when crossing the road concerned, and seeing bridge use as time saving and safe in general were positively related to respondents' bridge use. In addition, the pedestrian bridge designs, signboards, fences, and speed of vehicle which leads to the pedestrian's comfort and safety, also play some important roles on the effectiveness of pedestrian bridge utilization. The finding from this study, there are various measures to increase the pedestrian's bridge use. Addition the site study area should be done to get the good result.